Floating objects with finite resistance to bending. - Vella, D (2008)
We consider the equilibrium flotation of a thin, flexible cylinder at the interface between a liquid and a gas. In particular, we determine the maximum load that such a cylinder can support without sinking. We find that as the length of such a cylinder increases the maximum load at first increases. However, the maximum load reaches a plateau when the length of the cylinder is comparable to the elastocapillary length, which is determined by a balance between the bending of the cylinder and surface tension. We then consider the implications of our analysis for the walking on water of both arthropods and man-made robots. In particular, we show that the legs of water striders are typically slightly shorter than this 'optimal' length, suggesting that elastocapillary effects may act as a selection pressure.